Are we making a difference in primary care for adults with intellectual and developmental disabilities? - Hélène Ouellette-Kuntz; Glenys Smith; Casey Fulford; Virginie Cobigo (Pan American Health Organization, 2018)
Objectives. To examine the impact of the dissemination of guidelines to physicians and of a population-level health communication intervention on the percentage of adults with intellectual and developmental disabilities (IDD) receiving preventive care through primary care. Methods. Noninstitutionalized adults with IDD in the province of Ontario, Canada, aged 40 to 64 years were matched to Ontarians without such disabilities each fiscal year (FY) from 2003 to 2016. Health administrative data were used to create a composite measure of receipt of recommended preventive primary care. Age-adjusted rates were used to assess trends, and average two-year rate ratios (RRs) and confidence intervals (CIs) were used to evaluate the effectiveness of the interventions. Results. The number of adults with IDD identified ranged from 20 030 in FY 2003 to 28 080 in FY 2016. The percentage of adults with IDD receiving recommended preventive primary care ranged from 43.4% in 2003 to 55.7% in 2015. Men with IDD had a 53.7% increase across the 13 years, while women with IDD only had a 30.9% increase. When evaluating the impact of the interventions, men with IDD were 4% more likely (RR: 1.04; 95% CI: 1.02-1.05) to receive recommended primary care in FY 2015 and FY 2016 as compared to FY 2009 and FY 2010; in contrast, women with IDD were 5% less likely (RR: 0.95; 95% CI: 0.93-0.98). A comparable drop was observed among women without IDD. Conclusions. Nearly 45% of adults with IDD in Ontario still do not receive recommended preventive care through primary care. Long-term impacts of the interventions introduced in the province may still occur over time, so ongoing monitoring is warranted. Special attention should be given to the preventive care needs of women with IDD.